Operating Cash Flow, Earning Response Coefficient, and Fixed Asset Revaluation: Study on Manufacturing Company - Andison Andison; Etty M Nasser (Faculty of Economic and Business, 2017)
The purpose of this study to determine the effect of operating cash flow to the abnormal return and the effect of operating cash flow to the abnormal return of companies that conduct the revaluation is higher than that of non revaluation which adopted SFAS No. 16 (2012). The analysis used in this study are multiple regression, for the period 2012-2015. The results showed that operating cash flow has no effect on non-sampled companies revaluation, while the sample of firms that perform revaluation proves that operating cash flow has a positive and significant impact on the abnormal return. Moreover, the effect of revaluation policy can strengthen the influence between operating cash flow to the firm abnormal return than non revaluation.DOI: 10.15408/etk.v16i1.4820